Competitive Strategy Through SWOT Approaches at MSME Thasya Ethnic Lampung in Bandar Lampung - Firmansyah, Deni; Rr. Erlina; Faisol, Ahmad (Basecamp Economics PubMed, 2024)
Thasya Ethnic Lampung is a tapis cloth craft business that is innovated into several products ranging from clothes, bags, peci, pillow cases, tablecloths, and others. This study took the object of the Thasya Ethnic Lampung tapis craft MSME to find out how the competitive strategy of MSME is, and what can be an alternative strategy for Thasya Ethnic Lampung in facing the large number of competitors of the same type that cannot be controlled. Qualitative methods were used in the study by using an analysis tool in the form of SWOT. The results of the study showed that the condition of Thasya Ethnic Lampung was already in a condition where MSME only needed to carry out a strategy that was grow and build. The implementation of the strategy was in the form of developing a strategy from a strategy that had been used previously. Starting from the production aspect by continuing to improve, develop and always innovate related to products so that they survive and are not easily imitated by similar MSME. Furthermore, Thasya Ethnic Lampung can improve the service and marketing system with creative forms and in accordance with the development of the times and the needs of target consumers, so that it can reach a wider market. In the financial aspect, it can be complemented by improving the use of digital media as a tool for recording, calculating and storing transaction data.